Regional Potential-Based Project Learning in Entrepreneurship - Andi Saputra; Nismar Amini; Yudhistira Yudhistira; Nizwardi Jalinus; Hansi Effendi (Edumaspul: Jurnal Pendidikan, 2022)
Vocational education has an important role in the current industrial revolution 4.0. To be able to compete in the era of the industrial revolution 4.0, vocational education must have competency and skills-based learning program planning. The skills demanded in the 21st century are critical thinking skills, creativity, collaboration, and communication (4 C's). This is an effort to transform technology in the era of revolution 4.0 into vocational education. One of the learning innovations in applying the 4 C's can lead to development in exploring the potential of an area. Where students have the skills to produce products according to regional potential as a provision for the future in facing job competition in the era of revolution 4.0.